Перспективы обнаружения промышленных скоплений углеводородов Успеновской площади в Одесской области по данным исследований мобильными прямопоисковыми методами - Самсонов, А.И.; Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2017)
Анализируются перспективы обнаружения промышленных скоплений нефти и газа в Одесской обл. Полученные оценки базируются на результатах анализа материалов поисковых геолого-геофизических работ и бурения, а также данных исследований прямопоисковыми геоэлектрическими и дистанционным методами. На Успеновской поисковой площади проведены наземные исследования геоэлектрическими методами становления короткоимпульсного электромагнитного поля (СКИП) и вертикального электрорезонансного зондирования (ВЭРЗ). Съемкой методом СКИП в ее пределах выявлено 6 геоэлектрических аномалий типа “нефтегазовая залежь” общей площадью 98 км². Работами методом ВЭРЗ в контурах аномалий выделены аномальное поляризованные пласты типа “нефть” и “газ” в отложениях нижнего девона-силура и кембрия. Обследованная площадь высокоперспективна на обнаружение промышленных залежей нефти и газа. Поиски и разведка промышленных скоплений углеводородов на суше и освоение обнаруженных ресурсов существенно дешевле, чем в морских акваториях, поэтому обнаруженные аномальные зоны заслуживают детального изучения прямопоисковыми и традиционными геофизическими (в том числе сейсмическими) методами. Мобильную технологию частотно-резонансной обработки спутниковых снимков целесообразно использовать для рекогносцировочного обследования слабоизученных регионов Украины с целью оперативного обнаружения локальных участков для детального изучения. Проаналізовано перспективи виявлення промислових скупчень нафти і газу в Одеській обл. Отримані оцінки ґрунтуються на результатах аналізу матеріалів пошукових геолого-геофізичних робіт і буріння, а також даних досліджень прямопошуковими геоелектричними і дистанційним методами. На Успенівський пошуковій площі проведено наземні дослідження геоелектричними методами становлення короткоімпульсного електромагнітного поля (СКІП) і вертикального електрорезонансного зондування (ВЕРЗ). Зніманням методом СКІП в її межах виявлено 6 геоелектричних аномалій типу “нафтогазовий поклад” загальною площею 98 км². Роботами методом ВЕРЗ в контурах аномалій виділено аномально поляризовані пласти типу “нафта” і “газ” у відкладах нижнього девону—силуру і кембрію. Обстежена площа є високоперспективною на виявлення промислових покладів нафти і газу. Пошуки і розвідка промислових скупчень вуглеводнів на суші і освоєння виявлених ресурсів істотно дешевші, ніж у морських акваторіях, тому виявлені аномальні зони заслуговують на детальне вивчення прямопошуковими і традиційними геофізичними (в тому числі сейсмічними) методами. Мобільну технологію частотно-резонансної обробки супутникових знімків доцільно використовувати для рекогносцирувального обстеження слабовивчених регіонів України з метою оперативного виявлення локальних ділянок для детального вивчення. Purpose The paper deals with the application of mobile direct-prospecting technology for operative assessment of the prospects of oil and gas potential in the search area of the Odessa region, and the methods to improve hydrocarbons prospecting and exploration. Design /methodology /approach The approved mobile technology includes a frequency-resonance method of RS data (satellite images) processing and decoding, as well as the ground-based geoelectrical methods to form a short-pulse electromagnetic field (FSPEF) and vertical electric-resonance sounding (VERS). Separate components of the technology can be used at various stages of prospecting-reconnaissance (assessment of oil and gas prospects of large search blocks), detailed (assessment of predicted oil and gas resources within the individual anomalous zones discovered at the reconnaissance stage), field investigation (ground-based field studies by geo-electric methods of FSPEF and VERS with the view to clarifying the projected oil and gas resources and selecting the optimal locations for prospecting and exploratory wells). Findings In the Uspenovskaya exploration area, ground-based studies were carried out using the FSPEF and VERS geoelectrical methods. By the FSPEF method survey, 6 geoelectrical anomalies of the “oil and gas deposit” type, with a total area of 98 km² , were revealed within its contours. The anomalous polarized layers (APLs) of the “oil” and “gas” type in the sediments of the lower Devonian-Silurian and Cambrian, were identified in the contours of the anomalies by the VERS sounding. Within one of the mapped anomalies, we performed seismic CDP-2D investigations along two profiles. The interpretation and analysis of seismic materials showed that seismic CDP-2D prospecting allows us to solve the problem of studying the geological structure of the Uspenovskaya area to map a promising complex of Paleozoic formations (Silurian-Cambrian). Practical significance /implications The results of the conducted researches testify to the prospects of the Uspenovskaya area for prospecting and exploring industrial accumulations of oil and gas in the Lower Devonian-Silurian and Cambrian sediments. Since exploration for hydrocarbons onshore and development of the discovered resources are significantly cheaper than in offshore areas, the detected anomalous zones deserve a detailed study both by direct-prospecting technologies and by traditional geophysical methods (seismic, in the first place). Mobile geoelectrical methods of FSPEF and VERS can be used for detailed examination of prospective local areas in order to estimate the predicted oil and gas resources within their boundaries and to select sites for prospecting wells. The technology of frequency-resonance processing of satellite images is expedient for using in reconnaissance inspection of poorly studied regions of Ukraine and other countries with the purpose of operative detection of local areas for detailed study.